Investigation of wind characteristics and assessment of wind-generation potentiality in Uludag-Bursa, Turkey - Ucar, Aynur; Balo, Figen (Elsevier Sci Ltd, 2009)
In this study, wind characteristic and wind energy potential of the Uludag skinning which is located in the south Marmara region of Turkey were analyzed using the wind speed data collected during the period 2000-2006. The wind speed distribution curves of Uludag-Bursa were obtained by using the Weibull and Rayleigh probability density functions. The average Weibull shape parameter k and scale parameter c were found as 1.78 and 7.97 m/s for the period 2000-2006. The yearly mean wind speed in Uludag-Bursa was obtained as 7.08 m/s for period of 7 years. A technical and economic assessment has been made of electricity generation from four wind turbines having capacity of (600, 1000, 1500 and 2000 kW). The yearly energy Output, capacity factor and the electrical energy cost of kW h produced by the three different turbines were Calculated. The cost of each kW h produced using the chosen wind turbines in Uludag-Bursa were found to between 0.255 and 0.306 $/kW h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Weibull distribution; Electricity generation cost